Land Dispute Resolution through Mediation between Land Cultivators and Building Use Rights Holders in Semarang City (Indonesian Journal of Agrarian Law, 2026)
Land is a vital asset that is often the source of disputes, including overlapping disputes between cultivated land and land certified with Building Use Rights (HGB). This phenomenon occurs because there is still an overlap between physical control in the field and officially recorded legal data. This article aims to analyze the stages of mediation implementation in resolving land disputes at the Semarang City Land Office, as well as identify obstacles encountered and efforts that can be made to overcome them. This study uses an empirical legal method with a qualitative approach. Primary data was obtained through interviews with Young Land Administrators in the Dispute Control and Handling Section of the Semarang City Land Office. Mediation is carried out through structured stages, namely submitting an application, reviewing the case, clarifying the case, mediating the case, and determining the outcome. Mediation failed at the clarification stage because both parties insisted on maintaining their respective claims without any intention of compromising, so the parties were invited to resolve the case through the courts. The main obstacles found included initial refusal of mediation, the absence of one of the parties, and the lack of willingness to compromise. The success of mediation is not solely determined by the perfection of legal procedures, but is highly dependent on the good faith of the parties. Therefore, intensive socialization efforts, strengthening the capacity of mediators, and regular evaluation of failed mediation cases are needed to increase the effectiveness of non-litigation land dispute resolution.